Fluid and electrolyte balance during two different preseason training sessions in elite rugby union players - Cosgrove, S. D.; Love, T. D.; Brown, R. C.; Baker, D. F.; Howe, A. S.; Black, K. E. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to compare fluid balance between a resistance and an aerobic training sessions, in elite rugby players. It is hypothesized that resistance exercise will result in a higher prevalence of overdrinking, whereas during the aerobic session, underdrinking will be more prevalent. As with previous fluid balance studies, this was an observational study. Twenty-six players completed the resistance training session, and 20 players completed the aerobic training session. All players were members of an elite rugby union squad competing in the southern hemisphere's premier competition. For both sessions, players provided a preexercise urine sample to determine hydration status, pre- and postexercise measures of body mass, and blood sodium concentration were taken, and the weight of drink bottles were recorded to calculate sweat rates and fluid intake rates. Sweat patches were positioned on the shoulder of the players, and these remained in place throughout each training session and were later analyzed for sodium concentration. The percentage of sweat loss replaced was higher in the resistance (196 ± 130%) than the aerobic training session (56 ± 17%; p = 0.002). Despite this, no cases of hyponatremia were detected. The results also indicated that more than 80% of players started training in a hypohydrated state. Fluid intake seems to differ depending on the nature of the exercise session. In this group of athletes, players did not match their fluid intakes with their sweat loss, resulting in overdrinking during resistance training and underdrinking in aerobic training. Therefore, hydration strategies and education need to be tailored to the exercise session. Furthermore, given the large number of players arriving at training hypohydrated, improved hydration strategies away from the training venue are required.